16xy, 24x^2y^2 are two expressions with gcf of 8xy.
Answer : A {-8}
-4 = b/2
-4 *2 = b
-8 = b
Let x be the 1st number
x + 9 be the second number
Equation:
x + x+9 = 171
Solution:
2x + 9 = 171
2x = 171 - 9
2x = 162
x = 81
x + 9 = 90
81 + 90 = 171
Less then i really hope i helped
With some simple rearrangement, we can rewrite the numerator as
![2x^3 - 3x^2 - x + 4 = 2(x^3 - x) - 3x^2 + x + 4 \\\\ ~~~~~~~~ = 2x(x^2-1) - 3(x^2 - 1) + x + 1 \\\\ ~~~~~~~~ = (2x-3)(x^2-1) + x+1](https://tex.z-dn.net/?f=2x%5E3%20-%203x%5E2%20-%20x%20%2B%204%20%3D%202%28x%5E3%20-%20x%29%20-%203x%5E2%20%2B%20x%20%2B%204%20%5C%5C%5C%5C%20~~~~~~~~%20%3D%202x%28x%5E2-1%29%20-%203%28x%5E2%20-%201%29%20%2B%20x%20%2B%201%20%5C%5C%5C%5C%20~~~~~~~~%20%3D%20%282x-3%29%28x%5E2-1%29%20%2B%20x%2B1)
Then factorizing the difference of squares,
, we end up with
![\dfrac{2x^3 - 3x^2 - x + 4}{x^2 - 1} = \dfrac{(2x-3)(x-1)(x+1) + x+1}{(x-1)(x+1)} \\\\ ~~~~~~~~ = \boxed{2x-3 + \dfrac1{x-1}}](https://tex.z-dn.net/?f=%5Cdfrac%7B2x%5E3%20-%203x%5E2%20-%20x%20%2B%204%7D%7Bx%5E2%20-%201%7D%20%3D%20%5Cdfrac%7B%282x-3%29%28x-1%29%28x%2B1%29%20%2B%20x%2B1%7D%7B%28x-1%29%28x%2B1%29%7D%20%5C%5C%5C%5C%20~~~~~~~~%20%3D%20%5Cboxed%7B2x-3%20%2B%20%5Cdfrac1%7Bx-1%7D%7D)